Destigmatization Through Visualization: Striving to redefine refugee workers' worth. Issue 5 (May 2023) - Bullinger, Bernadette; Schneider, Anna; Gond, Jean-Pascal
Refugee workers struggle to find employment because they are stigmatized. Research suggests that organizations can help de stigmatize actors such as refugees by recognizing them and confirming their worth in society. Here, we explore pictures that refugee job-placement organizations in Austria and Germany used to redefine refugees' moral worthiness – that is, their worth in relation to higher-order normative principles such as civic duty, efficiency and creativity. Analysing images used in organizations' destigmatization efforts is essential, as pictures visualize and materialize refugees rather than abstractly describing them. Hence, visualization shapes the worthiness of refugee workers in the eyes of prospective employers. Combining social semiotics with the economies of worth framework, we found that job-placement organizations use three visualization practices – professionalizing, domesticizing and stylizing – that draw on distinct moral orders. We found that although these practices were intended to destigmatize, they also – counterintuitively – restigmatize. By leveraging social semiotic studies of visualization, our results advance stigmatization studies by showing how visualization can unintendedly restigmatize and by revealing that the visualization practices we identified are built upon multiple forms of worth. Our analysis also theoretically and methodologically extends studies of organizational morality by explaining how moral dimensions are expressed through visual registers.